Некоторые особенности имплантации в условиях применения клеточных технологий - I. V. Maiborodin; S. V. Khomenyuk; T. V. Mikheeva; G. Yu. Yarin; V. I. Maiborodina; M. K. Agzaev; I. A. Vilgelmi; A. I. Shevela (Клінічна хірургія)
Некоторые особенности имплантации в условиях применения клеточных технологий